2014
DOI: 10.1002/14651858.cd011431
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic tests for diagnosing uncomplicated non-falciparum or Plasmodium vivax malaria in endemic countries

Abstract: BackgroundIn settings where both Plasmodium vivax and Plasmodium falciparum infection cause malaria, rapid diagnostic tests (RDTs) need to distinguish which species is causing the patients' symptoms, as different treatments are required. Older RDTs incorporated two test lines to distinguish malaria due to P. falciparum, from malaria due to any other Plasmodium species (non-falciparum). These RDTs can be classified according to which antibodies they use: Type 2 RDTs use HRP-2 (for P. falciparum) and aldolase (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 367 publications
2
80
0
2
Order By: Relevance
“…32 Heterogeneity (measured by I 2 values) was reduced by stratifying WSTs by presentation method (ie, single sips, consecutive sips, progressive volume challenges) and by the patient's clinical response. To avoid bias of repeated analyses of the same patient, 33 we randomly selected a single outcome when studies reported multiple outcomes using the same index test. [34][35][36][37] Causes for heterogeneity were investigated using meta-regression via the MIDAS program 38 in Stata version 12.1 (StataCorp), with an a priori significance of P < .05.…”
Section: Resultsmentioning
confidence: 99%
“…32 Heterogeneity (measured by I 2 values) was reduced by stratifying WSTs by presentation method (ie, single sips, consecutive sips, progressive volume challenges) and by the patient's clinical response. To avoid bias of repeated analyses of the same patient, 33 we randomly selected a single outcome when studies reported multiple outcomes using the same index test. [34][35][36][37] Causes for heterogeneity were investigated using meta-regression via the MIDAS program 38 in Stata version 12.1 (StataCorp), with an a priori significance of P < .05.…”
Section: Resultsmentioning
confidence: 99%
“…Good-quality RDTs capable of detecting both species have become increasingly available in areas where the two species coexist 45. The cost of RDTs has been declining over time46 with pan-specific tests available in the range of 1–2 U.S.…”
Section: Costs and Cost-effectiveness Of Diagnosis And Treatmentmentioning
confidence: 99%
“…The performance of RDTs is very often analysed from the clinical point-of-view: the capacity of RDTs to identify correctly malaria positive and negative samples is evaluated in comparison to a reference method, such as light microscopy or PCR, and diagnostic sensitivity and specificity values are reported with associated confidence intervals [5, 6]. Little is known however, about the analytical performance of RDTs, especially the analytical sensitivity, which corresponds to the lowest detectable concentration of the target analyte.…”
Section: Introductionmentioning
confidence: 99%